Implementasi Kebijakan Pengelolaan Dana Desa pada Kecamatan Bunguran Tengah Kabupaten Natuna - Wahyu Saputro; Razaki Persada; Mani Festati Broto (Syntax Literate, 2023)
The Village Fund policy is intended for villages to finance the implementation of village governance. For more than three years, the priority use of the Village Fund has been directed towards stunting prevention. However, it was identified that stunting prevention in three villages in Bunguran Tengah sub-district is still high. The assumption is that with the management of the Village Fund for stunting prevention in the three villages, it will decrease, if this continues, it will risk decreasing the level of productivity in the three villages. The purpose of this study is to analyze the implementation of the Village Fund Management Policy in Bunguran Tengah Sub-district, Natuna Regency, including an analysis of the factors that influence policy implementation, factors that hinder policy implementation, and efforts to overcome factors that hinder policy implementation. The theory used as a basis for examining the focus of research, namely Policy Implementation Theory using the Donald P. Warwick Model, includes Enabling Factors consisting of Organizational Commitment, Organizational Capability, Information Quality, and Potential. The inhibiting factors consist of the number of actors involved in policy implementation, low commitment or dual loyalty, the inherent complexity of the policy (instrinsic complexity), too long decision-making levels, time and leadership changes. This research was conducted using qualitative methods. The determination of informants in this study was carried out by purposive sampling, including the Head of Service, Sub-District Head, Village Head, Community Empowerment Expert, Village Facilitator, Community Development Cadre (KPM), Community Leaders. Data analysis will be carried out with descriptive analysis using the stages of data analysis according to Miles and Huberman. The results of this study indicate that the Village Fund Management Policy Implementation Process in Bunguran Tengah District, Natuna Regency, Riau Islands Province is running quite well, but not yet optimal. Influenced by factors of organizational commitment, organizational capability, quality of information, potential. Factors that hinder implementation include the low ability of human resources, Standard Operating Procedures in stunting prevention efforts in three villages have not been compiled as guidelines for the flow of work procedures, low commitment that occurs in leaders and implementers, decision-making levels that are too long, changes in leadership mean there is also the possibility of policy changes and the unavailability of supporting equipment, this results in less effective management of the Village Fund.